Features of the Supramolecular Cell-Genetic Organization of E. Coli in Engineering Aspects of Biotechnology - Ivanova, Evilina Alekseevna (KnE Life Sciences, 2022)
Recently, there has been a keen interest in the physicochemical features of self-organizing spatio-temporal, heteropolymer-supramolecular assemblies, in which the system of components of the fluctuation dynamics of surface protein groups is evolutionarily selected for the implementation of morphogenetic processes of ontogenesis.That is, evolution created chemical compounds, the exceptional organization of which ensured the fulfillment of the most complex and precise tasks.In this research, the bacterial cell ofE. coli was considered in the concept of supramolecular science, where, in accordance with the informational development program based on the principles of molecular recognition, phase ensembles appear, which are characterized by a certain organization, depending on the phase growth of the population culture. In this respect, proteomic super-molecular physicochemistry can be considered as physicochemical or molecular informatics.Arginine is of interest because almost all of its molecule is active and undergoes obligatory interactions both with DNA and with other histones and non-histones. The results of this study demonstrated the super-protein surface of supramolecular assemblies, the flexible system PPCС-E.coli, active zones, dynamics of continuity, positioning topologicalspatio-temporal Arg-protease-processing, local areas of the nucleoid system, and interrelations at the level of: Bp-liquid crystal-bacterioplasma; NsCo-fragile, PsCo-tightly bound to the cell remainder; and in the Co-cell remainder itself. These data may be of practical interest in various engineering aspects of biotechnology. Keywords: arginine protease processing, supramolecules, E.coli, phase protein, super-molecules.